(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The rapid advancement of Information Technology (IT) has revolutionized various sectors, including education. Rural education, traditionally limited by geographic and economic constraints, has experienced significant transformation due to the integration of IT. This paper explores the impact of IT on rural education, analyzing its role in improving accessibility, enhancing learning quality, bridging the digital divide, and addressing challenges related to infrastructure and digital literacy. The study also examines policy implications and future trends in the application of IT for educational advancement in rural areas.